2022
DOI: 10.1177/17470218221089964
|View full text |Cite
|
Sign up to set email alerts
|

Judging accidental harm: Reasoning style modulates the weight of intention and harm severity

Abstract: When judging a perpetrator who harmed someone accidentally, humans rely on distinct information pertaining to the perpetrator and victim. The present study investigates how reasoning style modulates the contribution of the victim’s harm and the perpetrator’s intention to third-party judgment of accidental harm. In two pre-registered online experiments, we simultaneously manipulated harm severity and the perpetrator’s intention. Participants completed reasoning measures as well as a moral judgment task consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…Importantly, data quality analyses confirmed the expected and well‐known negative relationship between cognitive reflection (as measured with CRT) and our core dependent variables (i.e. judgement severity in accidental harm transgression scenarios; Patil & Trémolière, 2021; Schwartz et al, 2022; Schwartz et al, under review). In addition, we were also able to show a positive association between cognitive reflection and our independent variables (i.e.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Importantly, data quality analyses confirmed the expected and well‐known negative relationship between cognitive reflection (as measured with CRT) and our core dependent variables (i.e. judgement severity in accidental harm transgression scenarios; Patil & Trémolière, 2021; Schwartz et al, 2022; Schwartz et al, under review). In addition, we were also able to show a positive association between cognitive reflection and our independent variables (i.e.…”
Section: Discussionsupporting
confidence: 71%
“…Of importance in regard to our current purpose is the growing support for the role of reasoning and cognitive deliberation in predicting the way people address accidental harm transgressions. It was observed for instance that people who were more deliberative were more lenient to accidental harm transgressions (Patil & Trémolière, 2021; Schwartz et al, 2022; Schwartz et al, under review). In the same vein, it was observed that more open‐minded people (as measured with the Actively Open‐Minded Thinking scale, which captures people's disposition to reason based on reflection rather than intuition; Baron et al, 2015; Stanovich & West, 1997, 2007) were more lenient to accidental harm transgressions (Schwartz et al, under review).…”
Section: Introductionmentioning
confidence: 99%
“…However, response change in more deliberative reasoners did not interact with the type of transgression but was observed across trials. This result is hard to reconcile with a similar line of work which showed that more deliberative participants, or participants with a greater need for cognition, may be more sensitive to the agent's intention to harm (Schwartz et al, 2022), judging the perpetrator's behavior less wrong following accidental harm, but more wrong following intentional harm. As Experiment 2 did not replicate the effect of reasoning style despite a larger sample size, we refrain to conclude that higher disposition toward deliberative thinking is associated with slower processing of intentionality.…”
Section: Individual Differences In the Dynamics Of Moral Judgmentsmentioning
confidence: 65%
“…Allowing participants to deliberate longer before giving their judgment of an agent's behavior may enable inferences about the moral character of the agent, which may in turn increase the severity at the second judgment. Previous work has for instance documented that following a negative outcome, people are more likely to attribute a bad moral character to the agent (Knobe, 2005), and increased severity toward individuals with a bad moral character has been found to be mediated by perceived intentionality (Schwartz et al, 2022). Additionally, even in the absence of a negative outcome, extra time to judge the agent may favor the engagement of theory of mind mechanisms (or lead participants to carry through theory of mind analyses with greater facility) to infer the agent's intention and reach the final judgment.…”
Section: The Distinct Dynamics Of Wrongness and Punishment Judgmentsmentioning
confidence: 99%
“…Indeed, as recently proposed by Hirschfeld-Kroen et al (2021) , Accidental Harm scenarios are an important context for broadening our understanding of the relation between agency and moral judgments thanks to the incongruence between the agent’s intention, which is neutral, and the action’s outcome, which is instead negative ( Young and Saxe, 2009 ). Indeed, for judging these scenarios, people must inhibit a salient and prepotent representation (i.e., the observed outcome for the victim) and assign more weight to a less immediate alternative (i.e., the intention of the agent; Young and Saxe, 2009 ; Margoni and Surian, 2016 , 2021 ; Baez et al, 2018 ; Schwartz et al, 2021 ). Thus, the pattern of correlations that we observed may suggest that people with stronger SoA fail to inhibit outcome/victim-based emotional processes.…”
Section: Discussionmentioning
confidence: 99%